Methodological development for 87Sr/86Sr measurement in olive oil and preliminary discussion of its use for geographical traceability of PDO Nîmes (France). (15th March 2015) - Medini, Salim; Janin, Myriam; Verdoux, Patrick; Techer, Isabelle
Highlights: The authenticity and identification of food have become a necessity. The lack of geographical identification protocol of olive oils can cause fraud and health risk. Establishing a protocol for extracting strontium in oils. The protocol proved to be efficient to reach a 87 Sr/ 86 Sr signature in PDO Nimes olive oil sample. The protocol of sr extraction in olive oil is applies to test a geographical discrimination. Abstract: The lack of a geographical identification protocol for olive oils can lead to fraud and health risks. As some works call for Sr isotopes for the geographical identification of agri-food products, this study focus on the feasibility of extracting Sr from olive oils for isotopic measurements by TIMS. In fact, existing protocols for purification of Sr are unsuitable for lipid matrix. The defined protocol is applied to samples of PDO Nîmes olive oil. The accuracy of the extraction procedure is tested against isotopic standards. The values obtained are in conformity with NIST certified values. This consistency demonstrates that no modification of 87 Sr/ 86 Sr ratio is brought about by this protocol. Consequently, the method is preliminary used on PDO Nîmes and Moroccan oils to evaluate the feasibility of a discriminant Sr signature on the two geographical products. This study provides promising results for the geographical discrimination and identification of PDO olive oils.